THE IMPLICATIONS OF MYANMAR’S MILITARY COUP ON THAILAND’S SECURITY SITUATION - Rahmadita, Nova Mei; Ash Shiddiqy, Muhammad Arsy (Department of International Relations Universitas Satya Negara Indonesia, 2025)
The military coup in Myanmar in 2021, had profound effects not only on the country but also on its neighboring countries, particularly Thailand. This study examines the coup’s impact on the security, economy, and diplomatic relations between Myanmar and Thailand. Through qualitative research and literature study, the study reveals that the coup led to a humanitarian crisis, large-scale refugee movements, cross-border security issues, and negative economic consequences. Thailand encountered difficulties in managing the influx of refugees, combating drug trafficking, and maintaining socio-economic stability along its border. In response, Thailand adopted a pragmatic diplomatic strategy, including a “Quiet Diplomacy” policy, to preserve bilateral relations and reduce tensions. Despite facing criticism for potentially legitimizing the military junta, Thailand sought to mediate the conflict. The study concludes that Myanmar’s military coup influences domestic security and the geopolitical and economic landscape of the region, necessitating attention and strategic actions from the international community. This research contributes to enriching literature on the impacts of Myanmar’s military coup to its neighboring countries and the dynamic of security in Southeast Asia.